PROFIL KEMAMPUAN LITERASI KUANTITATIF CALON GURU MATEMATIKA - Isna Rafianti; Yani Setiani; Novaliyosi Novaliyosi (JPPM (Jurnal Penelitian dan Pembelajaran Matematika), 2018)
ABSTRACTThe purpose of this research is to know the profile or description about the quantitative literacy ability of the students of mathematics prpspective teacher at Universitas Sultan Ageng Tirtayasa semester V of academic year 2017/2018. Quantitative literature closely related with everyday life so that this ability is very important to be owned by students and the next generation of the nation. Prospective math teachers should be able to evaluate themselves about the ability of quantitative literacy so that when a teacher can transfer these abilities to his students. This research uses descriptive research. Quantitative literacy indicators used include interpretation, representation, calculation (counting), assumptions, application / analysis and communication. Furthermore, the category of quantitative literacy ability of candidates for mathematics students is categorized as being with a value of 68.82. Keywords: Profile, Quantitative Literacy, Prospective Teacher